INDIAN IT FIRMS CREATING MANAGEMENT CODES FOR FOREIGN EXCHANGE RISK - Shankar, Nitin; Beena, Fatima (Indian Journal of Finance and Banking, 2021)
Purpose: India has been a preferred I.T. service sourcing nation globally and has been registering high growth. India has a significant pie of the global sourcing market, accounting for nearly 55 % share. It covers significant global through its more than one thousand centres spread across continents. With a year-on-year growth of 6.1%, India’s I.T. and ITES industry will increase to the U.S. 350 million by 2025. The extensive expanse of geographical coverage also translates into foreign exchange risk; hence foreign exchange risk management becomes an important strategy. The current study attempts to assess the impact of foreign exchange risk management on the Indian sector over 2007-2017; the period includes the 2008 financial crisis taken up in the current study. Design/Methodology/ Approach: We analyzed the Indian I.T. companies listed on the BSE Ltd on their exposure, approach, and management towards foreign exchange risk. We investigated their annual reports from 2007 -2017 to understand their exposure and the adopted external foreign exchange risk management techniques. We further assessed the impact of these foreign exchange risk management techniques on the firm’s value. Findings: The impact of foreign exchange risk management was significant on small-cap I.T. companies for the study period. Though for the during the 2008 crisis term, it was found to be insignificant. Practical/Implications: Foreign exchange risk management is crucial for Indian I.T. companies indulging in cross-border trade. The current study incorporates external methods of managing foreign exchange risk management; hence even if the impact were found to be insignificant for Mid Cap and some Large-cap companies, they would be practicing internal hedging methods, which puts a strong case tapping trillion-dollar business through a fully functional competitive International Financial Centre. Originality/Value: Our paper contributes to the literature on Foreign exchange risk management by Indian I.T. companies, which contributes handsomely to India’s GDP and Foreign exchange reserve. JEL Classification Codes: F31, G32.